Experimental investigation of the drainage characteristic and stability mechanism of gel-stabilized foam used to extinguish coal fire. (1st April 2022) - Shi, Quanlin; Qin, Botao; Xu, Yizhen; Hao, Mingyue; Shao, Xu; Zhuo, Hui
Highlights: The dynamic drainage process of gel-stabilized foam was investigated. The stability characteristic and mechanism of gel-stabilized foam were revealed. Three-stage drainage process was used to show stability of gel-stabilized foam. The thermostability of the foam were tested by exposing foam to coal fire. Abstract: For further clarifying the stability characteristic of gel-stabilized foam (GSF), the foam half-life, drainage process, microcosmic liquid film structure, and stability mechanism were investigated in this paper. In addition, the thermostability and fire-resistance characteristics of GSF were also tested by exposing foam to high-temperature coal fire. The results indicated that the GSF exhibited the special three-stage drainage process of GSF, different from the two-stage theory of traditional two-phase foam (TTF). The enhanced foam stability was mainly ascribed to the formation of gel structure in GSF system by chemical crosslinking reaction, which provided larger resistance to the liquid drainage in bubble film dominated by gravity, finally resulting in zero drainage before 60 h. Moreover, SEM-EDS analysis revealed that the gelified film of gel-stabilized foam contained O, C, and Na elements (more than 95 wt%), mainly deriving from polymer and surfactant molecules in the raw materials of foam. Microstructure and theoretical analysis revealed that gelified film in GSF could delay the coarsening rate of bubbles, slow down its drainage rate, as well as reduce the coalescence and rupture rate of foam. Due to the enhanced foam stability after forming gel in liquid film, the GSF showed the superior fire-resistance characteristic and coverage effect on the heat source, and the foam could remain stable within 30 min even heating by coal-burning furnace. The gel-stabilized foam demonstrated the good application prospect for covering the burning coal to isolate oxygen and reduce temperature to extinguish coal fire.